Senp1 drives hypoxia-induced polycythemia via GATA1 and Bcl-xL in subjects with Monge’s disease - Azad, Priti; Zhao, Huiwen W.; Cabrales, Pedro J.; Ronen, Roy; Zhou, Dan; Poulsen, Orit; Appenzeller, Otto; Hsiao, Yu Hsin; Bafna, Vineet; Haddad, Gabriel G. (The Journal of experimental medicine, 2016)
In this study, because excessive polycythemia is a predominant trait in some high-altitude dwellers (chronic mountain sickness [CMS] or Monge’s disease) but not others living at the same altitude in the Andes, we took advantage of this human experiment of nature and used a combination of induced pluripotent stem cell technology, genomics, and molecular biology in this unique population to understand the molecular basis for hypoxia-induced excessive polycythemia. As compared with sea-level controls and non-CMS subjects who responded to hypoxia by increasing their RBCs modestly or not at all, respectively, CMS cells increased theirs remarkably (up to 60-fold). Although there was a switch from fetal to adult HgbA0 in all populations and a concomitant shift in oxygen binding, we found that CMS cells matured faster and had a higher efficiency and proliferative potential than non-CMS cells. We also established that SENP1 plays a critical role in the differential erythropoietic response of CMS and non-CMS subjects: we can convert the CMS phenotype into that of non-CMS and vice versa by altering SENP1 levels. We also demonstrated that GATA1 is an essential downstream target of SENP1 and that the differential expression and response of GATA1 and Bcl-xL are a key mechanism underlying CMS pathology.